Treatment of Acute Myeloid Leukemia During Pregnancy. (January 2015) - Chang, Abraham; Patel, Samit
Objectives: Systematically review the literature assessing outcomes of acute myeloid leukemia (AML) treatment during pregnancy.Data Sources: A Pubmed literature search (January 1969 to June 2014) for articles written about AML and pregnancy, and bibliographies/citations of previously published reviews.Study Selection and Data Extraction: Articles written in the English language that administered active AML chemotherapy during pregnancy were included.Data Synthesis: Eighty-five fetuses were exposed to chemotherapy from 83 mothers: 8 mothers began induction chemotherapy in the first trimester, 61 mothers in the second trimester, and 14 mothers in the third trimester. Chemotherapy resulted in more fetal deaths and spontaneous abortions during the first trimester (37.5%) compared with the second (9.7%) and third trimesters (0%). All cases included cytarabine; 47 fetuses were exposed to daunorubicin and 8 fetuses to idarubicin. The percentages of fetal defects and death for cytarabine and daunorubicin combinations were 8.5% and 6.4%, respectively. With cytarabine and idarubicin combinations, the percentages of fetal defects and death were 28.6% and 12.5%, respectively. Complete remission (CR) rates were 100%, 81%, and 67% in the first, second, and third trimesters.Conclusions: Treatment during the second and third trimesters resulted in fewer fetal complications than the first trimester. However, delaying AML treatment may adversely affect the mother's outcomes. In the reported cases, induction during pregnancy resulted in CR rates comparable to that in nonpregnant patients. The choice of anthracycline is still unclear, but the decision should be made with careful consideration, weighing the outcomes for the mother and fetus.